2021
DOI: 10.1016/j.jbef.2021.100574
|View full text |Cite
|
Sign up to set email alerts
|

FinTech payments in the era of COVID-19: Factors influencing behavioral intentions of “Generation X” in Hungary to use mobile payment

Abstract: Organizations, such as the World Health Organization, encouraged consumers to use contactless payment methods instead of payment methods such as cash, which can be carriers of the SARS-2 virus. This study aims to evaluate factors that influence Hungarian Generation X’s behavioral intentions to use mobile payment services during the pandemic. We conducted an electronic questionnaire-based survey among 1120 Generation X individuals. Using structural equation modeling to analyze the study’s conceptual model, our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
79
2
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(129 citation statements)
references
References 74 publications
16
79
2
2
Order By: Relevance
“…It means that an individual will act rationally using all available information and perform calculations either directly or indirectly. The TPB has been widely used by previous researchers to link the level of financial literacy with financial behavior (Arianti, 2017;Daragmeh et al, 2021;Meyliana et al, 2019;Normawati et al, 2021).…”
Section: Digital Financial Literacy and Financial Behaviormentioning
confidence: 99%
“…It means that an individual will act rationally using all available information and perform calculations either directly or indirectly. The TPB has been widely used by previous researchers to link the level of financial literacy with financial behavior (Arianti, 2017;Daragmeh et al, 2021;Meyliana et al, 2019;Normawati et al, 2021).…”
Section: Digital Financial Literacy and Financial Behaviormentioning
confidence: 99%
“…Several studies on mobile easy payment services found a positive relationship between PEOU and the intention to use mobile payment services. Cao et al (2016) , Shankar and Datta (2018) , and Daragmeh et al (2021) found that PEOU had the greatest effect on PU. Therefore, this study proposed the following hypotheses:…”
Section: Methodsmentioning
confidence: 97%
“…A study conducted in Hungary found that the COVID-19 pandemic affected the intention to use mobile easy payment services ( Daragmeh et al, 2021 ), where more than 80% of payments before 2019 were made in cash (before COVID-19). However, such findings are not generalizable, as in several countries, including South Korea, the utilization rate of mobile easy payment services was high even before the COVID-19 pandemic.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…COVID-19 negatively affected many industries but facilitated the development of the fintech sector [12]. Fintech increased the convenience of public lifestyles [4,5] and improved the productivity of businesses [6,7], which was more evident during the epidemic.…”
Section: Introductionmentioning
confidence: 99%